2018
DOI: 10.7883/yoken.jjid.2017.233
|View full text |Cite
|
Sign up to set email alerts
|

International Comparison of Causative Bacteria and Antimicrobial Susceptibilities of Urinary Tract Infections between Kobe, Japan, and Surabaya, Indonesia

Abstract: SUMMARY:Variation by country in urinary tract infection (UTI)-causative bacteria is partly due to the differences in the use of antibiotics. We compared their frequencies and antibiotic susceptibilities in the treatment of patients with UTI from 2 cities, Kobe, Japan, and Surabaya, Indonesia. We retrospectively analyzed 1,804 urine samples collected from patients with UTI in 2014 (1,251 collected in 11 months at Kobe University Hospital in Kobe and 544 collected in 2 months at Dr. Soetomo Hospital in Surabaya)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 28 publications
2
17
1
4
Order By: Relevance
“…We previously identified E. coli as the most common UTI pathogen in Indonesia in a comparison with Kobe. 7 Moreover, the ESBL production rates of E. coli and K. pneumoniae were high in Indonesia, and susceptibility to LVFX was poor, which is also similar to the current findings. Ampicillin, cephalosporins, and fluoroquinolones are choices for treating UTIs in Indonesia.…”
Section: Comparison Of Esbl-producing Bacteriasupporting
confidence: 88%
“…We previously identified E. coli as the most common UTI pathogen in Indonesia in a comparison with Kobe. 7 Moreover, the ESBL production rates of E. coli and K. pneumoniae were high in Indonesia, and susceptibility to LVFX was poor, which is also similar to the current findings. Ampicillin, cephalosporins, and fluoroquinolones are choices for treating UTIs in Indonesia.…”
Section: Comparison Of Esbl-producing Bacteriasupporting
confidence: 88%
“…[11][12][13][14] To investigate carbapenemase genes including NDM-1, IMP-7 and OXA-181, multiplex PCR (Hyplex SuperBug ID; Amplex, Gars am Inn, Germany) was used. This system can identify the phenotype of carbapenemase genes, such as bla VIM (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) , bla IMP and bla NDM-1 ; oxacillinase genes, such as bla OXA-48 -like encoding genes (including bla OXA-162 , OXA-181 , OXA.204 and bla OXA-244 ); and all variants of bla KPC(1-10) genes, as previously described. 15 DNA sequencing was carried out by Eurofins Genomics, Tokyo, Japan, after purification of PCR products by the QIAquick PCR Purification Kit (Qiagen, Hilden, Germany).…”
Section: Molecular Analysis Of Esbl Ampc and Carbapenemase Genes Usimentioning
confidence: 99%
“…A recent survey of eight Indonesian hospitals in 2016 (not yet published) showed that the occurrence of ESBL among Escherichia coli and Klebsiella pneumoniae (the most prevalent ESBL producers) ranged between 46% to 85%. Data from 2010 in three cities in Indonesia showed that 45% of E. coli and K. pneumoniae seen were ESBL ‐ producing, and that of 2014 showed a higher rate . ESBL‐producing bacteria are resistant to the third‐generation cephalosporin and monobactam/AZT, and in Indonesia the choice of antibiotics is limited to carbapenem, AMK, the combination of the third‐generation cephalosporin with β‐lactamase inhibitors (S/C and PIPC/TAZ), FOM and TGC…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bakteri ESBL E. coli dilaporkan sebagai patogen yang mengakibatkan diare pada beberapa kasus kesehatan di kota Surabaya (Wasito et al, 2017). Kitagawa et al (2018) juga melaporkan bahwa bakteri ESBL E. coli merupakan patogen dominan yang menyebabkan infeksi saluran kemih (ISK) pada pasien di rumah sakit Dr. Soetomo, Surabaya. Bakteri ini juga diketahui sebagai penyebab infkesi lain seperti pneumonia, abses, sepsis hingga infeksi kulit dan tulang (Natalia et al, 2018).…”
Section: Pendahuluanunclassified